FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGURAN DI KABUPATEN ACEH SELATAN TAHUN 2000-2021 - Nurva Belinda; Yayuk Eko Wahyuningsih (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
A country will never be separated from various problems that are certainly related to its citizens. Unemployment in Indonesia has reached tens of millions of people is an urgent problem that must be solved immediately because the impact of unemployment will be very dangerous for the order of social life. This study aims to determine the factors that influence the unemployment rate in South Aceh Regency in 2000-2021 by using the independent variables of PDRB growth rate, minimum wage and population. The data used in this study is secondary data obtained from BPS South Aceh Regency. This study uses a statistical descriptive analysis model and hypothesis testing through multiple linear regression analysis. The results showed that partially the PDRB growth rate variable had a negative and significant effect on the unemployment rate in South Aceh Regency, the minimum wage variable had a negative and significant effect on the unemployment rate in South Aceh Regency and the population variable had a positive and no significant effect on the unemployment rate. unemployment in South Aceh Regency. Simultaneously (F test), the PDRB growth rate, minimum wage and population have a significant effect on the unemployment rate, with a significance value (0.000 < 0.05). While the magnitude of the effect of the growth rate of PDRB, minimum wage and population on the unemployment rate is 78.8% and the remaining 21.2% is influenced by other variables not included in the research model